PERILAKU MASYARAKAT DI ERA DIGITAL (STUDI DI DESA WATUTUMOU III KECAMATA KALAWAT KABUPATEN MINAHASA UTARA) - NIKIJULUW, GABRIELLA MARYSCA ENJEL; RORONG, ARIE JUNUS; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study is about behavior in the digital age is in watutumou III village kalawat districnorth minahasa regency. The method of research used in this study is a descriptive study method with aqualitative approach. Data collection in this study is done through observation, interviews and documentcollection. While the data, analyzer techniques that researchers are using are qualitative with MilesHuberous approachis. Based on the results of research can be draw that is the behavior of society ih thedigital age especially in the watutumou III village has developed because it is in the digital age whichrequires us to enjoy and use the technology that exist today because of the use of gadgets themselves become a life style that belongs to every elemen of society. People’s understanding of useing gadgettechnology in the digital age has developed some societies have understood the use of these gadgetstechnology. The good effect that use of gadgets in the digital age has been feelt by gadget user and alsomakes it easiers for the job, get information, on business. Besides that use of gadges often has an effect oneyes health especially among children and the elderly.Keyword : Biographical Caracteristics, Ability, Learning.